A Comparative Study of the Effectiveness of the Circular Economy Approach in China and the Community-Based Approach in Indonesia in Plastic Waste Management - Rizka Saputro Nugroho; Muhammad Musyarrof Bik (Marasofi International Media and Publishing (MIMP), 2025)
Plastic waste remains a pressing global environmental challenge, with countries adopting various approaches to address it. This study aims to compare the effectiveness of China's circular economy (CE) strategy and Indonesia's community-based (CB) approach in managing plastic waste. Employing a qualitative comparative method, the research analyzes policy frameworks, case studies, and secondary data from both countries. The results reveal that China’s CE model, supported by centralized policy integration and technological innovation, achieves a recycling rate of 31%, demonstrating national scalability and efficiency. Conversely, Indonesia’s CB model promotes grassroots participation and behavioral change but faces limitations in policy consistency and scalability, with recycling rates ranging between 11–15%. Despite these differences, both approaches offer complementary strengths. China showcases systemic and industrial coordination, while Indonesia highlights the value of community engagement. This study recommends a hybrid strategy that combines China’s policy-driven structure with Indonesia’s participatory initiatives to create a more inclusive and sustainable plastic waste management model. The findings encourage policymakers and international agencies to promote knowledge exchange and develop integrated frameworks that balance regulation with public involvement.